PENGARUH VARIASI FRAKSI VOLUME TERHADAP SIFAT MEKANIK KOMPOSIT SERAT RAMBUT MANUSIA DAN SERBUK KAYU DENGAN MATRIKS EPOXY - Danendra, bisma arya (JEECAE (Journal of Electrical, Electronics, Control, and Automotive Engineering), 2025)
The development of the use of natural composites in the automotive field is growing. A composite is a combination of two or more materials that are assembled to enhance mechanical properties in order to produce superior materials. The use of natural fibers is widely used because of its relatively inexpensive and environmentally friendly price. In this study we will look at composites with human hair fibers and epoxy matrix wood powders with random fibers patterns and use hand lay-up methods with volume fractions variations of 30% : 0% : 70%, 25% : 5% : 70% and 20% : 10% : 70% to find out the mechanical properties and bounding bonds in them. In the impact and pull test, the specimens with the highest impact force and pull force were 30% : 0 % : 70% of the maximum impact force value of 0,01961 j/mm^2. The highest pull force value was 32,05 MPa. For bounding bonds in the composite showed that of the volume fraction variations 30% : 0% : 70%, 25% : 5% : 70% and 20% : 10% : 70% there were some voids and fibers pull out out affecting the specimen's own mechanical properties.